Три бронзові скарби із Закарпаття - Пеняк, П. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
The article deals with three hoards from the Transcarpathian Museum of Local Lore. These hoards were discovered near villages Vary and Velyka Bigan’ (Beregovo district) and Mukachevo. The hoard from Vary is dated by the author back to the end of Bronze Age – the beginning of Iron age (XII–XI c. B.C.); the hoard from Velyka Bigan’ – to the end of period C – the beginning оf period D of Bronze Age (end of XIII – beginning of XII c. B.C.); the hoard from Mukachevo – to Iron Age (XI–X c. B.C.).